Educational institutions and the development of the concept of social responsibility - Abdalqhadr, A.; Mihus, I.; Мігус, Ірина Петрівна (Університет «КРОК», 2020)
Increased competition in the higher education system due to globalization and the strengthening of the role of knowledge in society have led to the fact that higher education institutions, acting as integrating agents of society, have to solve specific tasks not inherent in them. In particular, the higher education system is designed not only to meet students' knowledge needs, but also to take into account the interests of a large number of other stakeholders (stakeholders) in producing knowledge and performing their functions, which in turn will allow higher education institutions to gain sustainable competitive advantage. and scientific services. The education system is balanced if the socio-economic interests are balanced and the actions of all institutions and actors are coordinated. If the education system is characterized by inequality or discrimination, society as a whole will be unstable. The solution of these problems is possible under the formation of a system of social responsibility -awareness oftheir social role, satisfaction of mutual obligations and requirements of major institutions and actors in the field of educational activities -the consumption of educational services, the formation of comprehensively developed, highly moral citizens. economic development of the country and its regions.This research aims to draw attention the role of educational institutions the promoting and Development of The Concept Of Social Responsibility among students, especially higher education students, So thatstudents become more responsible toward their colleagues and friends and families and universities and the society as whole, The researcher used the descriptive analytical approach, relying on previous studies that focused about important role of educational institutions in modifying and improvement behavior of students. The results showed that educational institutions have a prominent role in promoting social responsibility among students by adding some activities and variety ideas inside and outside theclassrooms.

Посилення конкуренції у системі вищої освіти внаслідок глобалізації та посилення ролі знань у суспільстві призвели до того, що заклади вищої освіти, виступаючи в ролі інтегруючих агентів суспільства, повинні вирішувати специфічні завдання, не притаманні їм раніше. Зокрема, система вищої освіти покликана задовольняти не лише потреби студентів у знаннях, але і враховувати інтереси великої кількості інших зацікавлених сторін (стейкхолдерів) при продукуванні знань і виконанні властивих їм функцій, що у свою чергу дозволить закладам вищої освіти отримувати стійкі конкурентні переваги на ринку освітніх і наукових послуг. Система освіти є рівноважною, якщо збалансовані соціальноекономічні інтереси й узгоджені дії всіх інститутів та акторів. Якщо система освіти характеризується нерівністю або дискримінацією, нестійким буде й усе суспільство. Вирішення цих завдань можливе за умови формування системи соціальної відповідальності –усвідомлення своєї суспільної ролі, задоволення взаємних зобов’язань і вимог основними інститутами та акторами освітньої сфери щодо результатів спільної діяльності з виробництва –споживання освітніх послуг, формування всебічно розвинених, високоморальних громадян з метою соціально-економічного розвитку країни та її регіонів. Данедослідження має на меті звернути увагу на роль навчальних закладів у просуванні та розвитку Концепції соціальної відповідальності серед студентів, особливо студентів вищої освіти, щоб студенти стали більш відповідальними перед колегами та друзями та родинами та університетами та суспільством загалом, Дослідник застосував описовий аналітичний підхід, спираючись на попередні дослідження, які зосереджувались на важливій ролі навчальних закладів у модифікації та вдосконаленні поведінки учнів. Результати показали, що навчальні заклади відіграють помітну роль у просуванні соціальної відповідальності серед учнів, додаючи деякі заходи та різноманітні ідеї всередині та поза класом
Keywords: development; educational institutions; social responsibility; activities classroom and extra-curricular; розвиток; навчальні заклади; соціальна відповідальність; діяльності аудиторії та позакласна робота